SHADOW ECONOMY AS A WAY OF BUSINESS SURVIVAL - Dyuzhilova, Mikhailovna; Samylina, Yulia; Tolstova, Irina; Kishko, Vladimir; Smirnova, Anastasiya (Revista Inclusiones, 2020)
The article deals with the functioning peculiarities of the shadow economy. It is established that economic reforms have required strengthening the role of the state in the economy and the dominance of the role of state entrepreneurship. In this case, the lack of protection of private property, the manifestation of imperfect competition, the decrease in the effectiveness of traditional mechanisms for providing the population with essential commodities, and the aggravation of contradictions between free private businesses and the state have led to systematic growth of shadow economic relations. It is proved that the shadow economic relations in business result from the discrepancy between the legal and regulatory framework of business and operations and the economic interests of entrepreneurs and the aspirations of the common population, which activates the shadow sector of the economy. It is revealed that shadow economic relations have played a progressive role to a certain extent, since they contributed to the formation of market economy institutions, the emergence and development of contemporary Russian business, while for the most vulnerable social strata of the population, this was a way of actual survival.